Blood Pressure Variability during Angiography in Patients with Ischemic Stroke and Intracranial Artery Stenosis. (1st September 2020) - Pan, Hui; Zhao, Rong; Liu, Feng-Di; Wu, Yi-Lan; Li, Ge-Fei; Shi, Yan-Hui; Liu, Yi-Sheng; Zhao, Ying; Zhuang, Mei-Ting; Hou, Tian-Yu; Zhang, Qi-Ting; Yao, Qian; et al.
Abstract : Our aim was to investigate factors predicting blood pressure (BP) variability during diagnostic cerebral angiography and associations between BP variability and clinical outcomes in patients with acute and subacute ischemic stroke and intracranial artery stenosis. 114 patients with ischemic stroke and intracranial artery stenosis (stenosis rate >50%) were recruited. Patients who underwent cerebral angiography within 3 days and 3–14 days of disease onset are referred to be Group A and Group S, respectively. BP variability in Group A was defined as the coefficient of variance (CV) of BP. Univariate and multivariate regression analyses were used to identify predictors of CV of BP and associations between CV of BP and clinical outcomes at discharge. In Group A patients, advanced age was associated with increased CV of SBP and diastolic blood pressure (DBP), and antihypertensive use was associated with lower CV of SBP. Male was associated with lower CV of DBP. In Group S, higher CV of SBP was associated with hypertension and antihypertensive use. Males had lower CV of SBP than females. The calcium channel blocker was associated with lower CV of DBP. Higher scores of the Stroke Scale at admission were significantly associated with poor clinical outcomes for both groups, while BP variability was not. Factors associated with BP variability are significantly different between stroke patients undergoing angiography within 3 days vs. 3–14 days after disease onset. BP variability is not significantly associated with clinical outcomes at discharge.